Hierarchical TiO2 spheres as highly efficient polysulfide host for lithium-sulfur batteries - Yang, Zhi-Zheng (Nature Publishing Group, 2016)
Hierarchical TiO2 micron spheres assembled by nano-plates were prepared through a facile hydrothermal route. Chemical tuning of the TiO2 through hydrogen reduction (H-TiO2) is shown to increase oxygen-vacancy density and thereby modifies the electronic properties. H-TiO2 spheres with a polar surface serve as the surface-bound intermediates for strong polysulfides binding. Under the restricting and recapturing effect, the sulfur cathode could deliver a high reversible capacity of 928.1 mA h g−1 after 50 charge-discharge cycles at a current density of 200 mA g−1. The H-TiO2 additive developed here is practical for restricting and recapturing the polysulfide from the electrolyte.